Brief Interventions for Hazardous and Harmful Alcohol Consumption in Accident and Emergency Departments - Wojnar, Marcin; Jakubczyk, Andrzej (Frontiers in Psychiatry, 2014)
The prevalence of alcohol abuse among patients treated in accident and emergency departments (A&E) is considered as substantial. This paper is a narrative review of studies investigating the effectiveness of brief interventions (BI) for hazardous and harmful alcohol consumption in A&E. A&E departments in hospitals (and other health care infrastructures) are commonly the place where serious consequences of alcohol drinking are seen and need to be tackled, supporting the suggested theoretical usefulness of delivering BI in this environment. Available research shows that BI may be considered a valuable technique for dealing with alcohol-related problems. However, it is suggested that the usefulness of BI may depend significantly on the target population to be dealt with. BI have proved to be beneficial for male individuals and those patients who do not abuse other psychoactive substances. In contrast, evidence indicates that BI in A&E settings are not effective at all when dealing with men admitted as a consequence of a violence-related event. In addition, some studies were unable to confirm the effectiveness of BI in female population, in emergency setting. Studies investigating the association between drinking patterns and the effectiveness of BI also present inconsistent results. Most studies assessing the effectiveness of BI in A&E settings only adopted a short perspective (looking at the impact up to a maximum of 12 months after the BI was delivered). When assessing the effects of BI, both the amount of alcohol consumed and expected reductions in alcohol consequences, such as injuries, can be taken into account. Evidence on the implementation of brief intervention in emergency departments remains inconclusive as to whether there are clear benefits. A variety of outcome measures and assessing procedures were used in the different studies, which have investigated this topic.